PENGEMBANGAN BAHAN AJAR MENULIS PUISI SEBAGAI UPAYA MEWUJUDKAN LITERASI SASTRA DI SEKOLAH DASAR - Muhammad Habibi; Chandra Chandra; Nana Fauzana Azima (FIP Unimed, 2019)
ABSTRACT This research is a type of development research (Research and The Development) which aims to produce poetry writing teaching materials using various valid creative techniques used in learning to write poetry. Based on the development activities and the results of the teaching material validation, it was concluded that the poetry writing materials using various creative techniques were declared valid and suitable for use in poetry writing learning in grade IV elementary school. Overall, the requirements for developing teaching materials have been fulfilled in the development activities carried out. Based on the validator's assessment of the aspects of content, language, presentation, and graphic feasibility. Teaching materials as a whole are suitable for use in an effort to improve students' skills in writing poetry. Keywords: Literacy, Teaching Materials ABSTRAKPenelitian ini merupakan jenis penelitian pengembangan (Research and The Development) yang bertujuan menghasilkan bahan ajar menulis puisi menggunakan berbagai teknik kreatif yang valid digunakan dalam pembelajaran menulis puisi. Berdasarkan kegiatan pengembangan dan hasil validasi bahan ajar, disimpulkan bahwa bahan ajar menulis puisi menggunakan berbagai teknik kreatif dinyatakan valid dan cocok untuk digunakan dalam pembelajaran menulis puisi di kelas IV SD. Secara keseluruhan, persyaratan untuk mengembangkan bahan ajar telah terpenuhi dalam kegiatan pembangunan yang dilakukan. Berdasarkan penilaian validator tentang aspek kelayakan konten, bahasa, presentasi, dan grafik. Bahan ajar secara keseluruhan sesuai untuk digunakan dalam upaya meningkatkan keterampilan siswa dalam menulis puisi.Kata Kunci: Literasi, Bahan Ajar